Language Situation in Kazakhstan in the Modern Period: Ideology, Policy and Planning - Stambulov Serik, Zhumanova Aiman,; Tolkynay, Sakabay; Karsybayeva Zhuldyz, Kentbek Salavat, (Opción, 2020)
This article presents the overall analysis of the contemporary language situation in the Republic of Kazakhstan. The principle of objectivity is the central approach of this article that considers historical phenomena and processes in details taking into account all contradictions. As a result, the authors would agree with those scholars who have a positive prognosis on language policy in Kazakhstan and affirm that all aims will be attained in the future. It is concluded that affirmative results of language policy are maintenance of balance between improvement of the state language status and compliance of other languages’ rights in multiethnic Kazakhstan